Electrical predictive model of Zener diode under pulsed EOS. Issue 4 (1st February 2015) - Zhu, F.; Ravelo, B.; Fouquet, F.; Kadi, M.
Abstract : Electrical overstress (EOS) is assumed as one of the most misinterpreted electrical phenomena that can affect drastically the reliability of electronic components. To predict the behaviour of a circuit under EOS, a relevant predictive circuit model is required. An investigation of circuit degradation caused by the pulsed EOS is addressed. More precisely, the electrical response of the Zener diode BZX84B6V8 under square wave EOS is modelled. The proposed model is originally extracted from the diode electro‐thermal behaviour caused by the self‐heating induced by excessive EOS on the reverse voltage. The diode EOS model was emulated and implemented in VHDL‐AMS language. It has been found experimentally, with a 17 V amplitude and 8 ms period square wave EOS, that the diode transient electrical parameters enable experimental response prediction. The suggested model can be used for reliability analyses of electronic devices.